THE IMPACT OF ARTIFICIAL INTELLIGENCE (AI) ON SYSTEMS MANAGEMENT INFORMATION - Ulya Salsabila; Intan Maulina; Rayyan Firdaus (RADJA PUBLIKA, 2025)
This study aims to systematically examine the impact of artificial intelligence (AI) on management information systems (MIS). Using the literature review method, relevant scientific articles, industry reports, and case studies are analyzed to identify trends, benefits, challenges, and potentials of AI in the context of MIS. The results of the analysis show that AI has a significant positive impact on operational efficiency, service personalization, and data-driven decision making. However, challenges such as the need for competent human resources, data security risks, and initial investment costs need to be managed properly. Future trends are toward the adoption of cloud-based AI platforms and more transparent and ethical AI technologies. This study provides comprehensive insights for academics and practitioners in understanding and implementing AI in management information systems.